2002
DOI: 10.1080/13548500220139449
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resistance factors as predictors of general health status and physical symptom reporting

Abstract: The ability of the psychological resistance factors Sense of Coherence (SOC) and dispositional Optimism (LOT-R) to predict physical symptom reporting (PILL), psychological wellbeing and perceived general health (SF-36Ò ), over and above demographic variables (age, race, gender) and the 'Big Five' personality dimensions (NEO-FFIÒ ) was explored in a sample of 202 undergraduate students. Hierarchical regression analyses identified race, Neuroticism, and Extraversion as significant predictors of physical sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 30 publications
(44 reference statements)
7
53
0
4
Order By: Relevance
“…As with the item-level analyses (Table 1), PCA was the most frequently used technique, with 9 of the 20 studies [18,[52][53][54]56,57,62,64,66] explicitly stating this method. Of the ten studies that mentioned the rotation method used, nine [18,21,[52][53][54][55]61,62,67] stated varimax, and one stated that they had used an oblique rotation [68]. Nine studies [17,21,58-60,63,65,67,68] only stated that they had used a factor analysis or exploratory factor analysis, and two studies had used a principal axis factor analysis [55,61].…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As with the item-level analyses (Table 1), PCA was the most frequently used technique, with 9 of the 20 studies [18,[52][53][54]56,57,62,64,66] explicitly stating this method. Of the ten studies that mentioned the rotation method used, nine [18,21,[52][53][54][55]61,62,67] stated varimax, and one stated that they had used an oblique rotation [68]. Nine studies [17,21,58-60,63,65,67,68] only stated that they had used a factor analysis or exploratory factor analysis, and two studies had used a principal axis factor analysis [55,61].…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
“…As with the item-level analyses, the samples were very diverse, and the sample sizes varied from 71 [52] to 1289 [17], with a mean of 288.70. Twelve studies [17,18,[52][53][54][55][56][57][58][59][60][61] reported that the turning to religion sub-scale loaded to a factor with at least one other sub-scale, three studies [62][63][64] reported that the turning to religion sub-scale formed its own separate factor, and five studies [21,[65][66][67][68] reported that the religion sub-scale did not have a sufficiently high loading with any other factor. As with the item-level analyses (Table 1), PCA was the most frequently used technique, with 9 of the 20 studies [18,[52][53][54]56,57,62,64,66] explicitly stating this method.…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
“…problem-focused behaviour) and negatively associated with ' maladaptive ' (e.g. denial) coping strategies (Amirkhan & Greaves, 2003;Ben-David & Leichtentritt, 1999;Cohen et al, 2008;Ebert et al, 2002;Edwards & Holden, 2003;Fok et al, 2005;Gallagher et al, 1994;Heiman, 2004;Johnson, 2004;Kalimo & Vuori, 1990;Kristensson & Ö hlund, 2005;Margalit et al, 1992;McSherry & Holm, 1994;Pallant & Lae, 2002).…”
Section: The Salutogenic Modelmentioning
confidence: 99%
“…Many authors use the LOT-R as bidimensional (Affleck, Tennen, & Apter, 2001;Chang, & Farrehi, 2001;Chang, & Sanna, 2003, Fontaine, & Cheskin, 1999 and others use it as unidimensional (Ebert et al, 2002;Harju & Bolen, 1998;Korkeila et al, 2004;Lai et al, 1998;Nelson, McMahon, Joffe, & Brensinger, 2003;Schou et al, 2004;van der Velden et al, 2007). Benyamini, (2005) focuses on the interaction of optimism and pessimism.…”
mentioning
confidence: 99%
“…Since the publication of the LOT in 1985, it has been used in several studies in health and personality psychology and has been linked to both psychological and physical well-being (Aspinwall, Richter, & Hoffman III, 2001;Ebert, Tucker, & Roth, 2002;Scheier & Carver, 1992). Chang and Sanna, (2001) in a study with middle-aged adults, found significant direct and indirect links between optimism and pessimism with depressive symptoms and life satisfaction; Segerstrom and Nes (2006) found better indices of psychological health accompanying better dispositional optimism ;Chang, (1998) found that dispositional optimism is a significant moderator of the relation between stress and psychological well-being.…”
mentioning
confidence: 99%